Peculiarities of primary school children's behaviour and their test anxiety - Augis, R. (Psichologija, 1988)
The test anxiety of 68 eight-year-olds has been conducted with the help of S. B. Sarason's "The Test Anxiety Scale for Children". The peculiarities of their behaviour in stress situations at school have been studied through clinical interviews and observations. The analysis of the data obtained has confirmed our hypothesis (p
Keywords: primary school children; test anxiety